Cold tolerance of subterranean clover in a continental-climate environment - Pecetti L.; Carroni A.M.; Piano E. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Subterranean clover is a suitable species as cover crop in vineyards and orchards. This alternative use requires the development of varieties with specific features. A sufficient level of cold tolerance might be needed to extend the area of utilization of subterranean clover in environments with low winter temperatures. Two cycles of evaluation for cold tolerance were carried out under field conditions at Lodi, northern Italy, on 24 genotypes singled out from Sardinian native populations, and five commercial cultivars. The native strains were chosen as to represent sites of origin with contrasting altitude and, within these, genotypes with contrasting earliness. Wide variation among genotypes was found in both seasons for cold susceptibility and winter growth ability, which could be usefully exploited for breeding. Late genotypes from high-altitude environments were generally the best performing strains.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)